REBRANDING PURAWISATA MENJADI MANDIRA BARUGA SEBAGAI UPAYA MENGEMBALIKAN BRAND IMAGE DESTINASI WISATA - , PRILITA ANDARINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Rebranding is derived from the word re- and branding. Re means again, while branding is the process of creating a brand image that connects the hearts and minds of customers. So rebranding is an effort made by the company to renew a brand that has been exist to make it better, by not ignore the original purpose of the company, which is profit oriented. The purpose of this study is to investigate the process promotion and marketing in Purawisata, find out the rebranding process and also find a formula to return the brand image in Purawisata. This study was conducted over three months and using collecting data method which done by observation, library research, interviews and qualitative methods of SWOT analisysis. The result of this study is to know the process of rebranding Purawisata to be Mandira Baruga as well as a business promotion and marketing efforts in order to create a brand image in accordance with the branding tourist destination.